The preliminary study on cassava (Manihot Esculenta) as gel polymer electrolyte for zinc-air battery - Zahid, A R M; Masri, M N; Hussin, M H; Abu Bakar, M B (2018)
The work investigates the characterization of cassava as gel polymer electrolyte for zinc-air battery. The usage of application energy storage such as battery are important due to energy renewable, emergency power supply and portable energy. Commonly, polymer gel electrolyte is not biodegradable and harmful to environmental. Besides, it also faces the problem of leakage that might affect short the life cycle of battery. To overcome the problem, cassava gel electrolyte with additional potassium hydroxide is potential and should be suitable material due to biodegradable and could prevent leakage. Preparation cassava gel electrolyte started by mixing cassava powder with deionized water before heated to gelling form present. The cassava gel then mixed with different KOH concentration forming cassava GPE. The ionic conductivity, viscoelastic and window stability were evaluated using varying cassava amount and KOH concentration. Conductivity value of pure cassava gel increase drastically after adding KOH solution. The highest ionic conductivity of cassava GPE recorded was at 6 M KOH. The viscosity of cassava GPE was remain constant and does not shown high different in value as the concentration KOH was increased.